(untitled) (Nigerian Journal of Technology, 2014)
Spatial flow patterns and quality trends for groundwater in Southwestern Nigeria have been undertaken with inadequate depth of interpretation. In this study, the geographical locations of wells and respective elevation were recorded using a Global Positioning System (GPS). Well depth and water level measurements were also obtained using measuring tape. Electronic meters were employed to determine temperature, salinity, hydrogen ion concentration (pH), Total Dissolved Solids (TDS) and electrical conductivity of 109 raw water samples. Geographical Information System (GIS) softwares (Arc View 3.3 and Surfer 8) were employed in the spatial data analyses. Results show that the groundwater flows towards the Southwest and Lower Mission in the Northwest, Orita in the East and Orita-TREM in the West. The pH ranges from 6.5 to 9.5 while TDS varies between 4.81 and 483.55 mg/l. The use GIS has proved to more precise in terms of positional accuracy, than the conventional map analysis